From the European Monetary Union to a euro–bancor: a stock–flow consistent assessment - Jacques Mazier; Sebastian Valdecantos (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2019)
The crisis of the euro area has questioned the fairness, sustainability and viability of the current setting of the European Monetary Union (EMU). In this article we use a four-country stock–flow consistent (SFC) model in the tradition of Godley/Lavoie (2007a) to examine to what extent an adaptation to Europe of Keynes's plan of a clearing union with bancor balances could help reduce the imbalances that, at least in part, drove the eurozone into crisis. Our simulation experiments suggest that the implementation of Keynes's ideas may conduct European countries to a stronger and more sustainable growth cycle.
Keywords: C63; E12; F33; 330; eurozone crisis; TARGET2; bancor; clearing union